Fuzzy power aggregation operators and their application to multiple attribute group decision making - Wei, Guiwu; Zhao, Xiaofei; Wang, Hongjun; Lin, Rui (Technological and Economic Development of Economy, 2013)
The article investigates the multiple attribute group decision making (MAGDM) problems in which the attribute values take the form of triangular fuzzy information. Motivated by the ideal of power aggregation, in this paper some power aggregation operators for aggregating triangular fuzzy information are developed and then applied in order to develop some models for multiple attribute group decision making with triangular fuzzy information. Finally, some illustrative examples are given to verify the developed approach and to demonstrate its practicality and effectiveness.